shadsiei

Answered question

2021-10-15

Let $A=\left[\begin{array}{ccc}4& 0& 5\\ -1& 3& 2\end{array}\right]$
$B=\left[\begin{array}{ccc}1& 1& 1\\ 3& 5& 7\end{array}\right]$
$C=\left[\begin{array}{ccc}2& & -3\\ 0& & 1\end{array}\right]$
Find $3A–B;C\cdot B+A.$

Answer & Explanation

Bentley Leach

Skilled2021-10-16Added 109 answers

$A=\left[\begin{array}{ccc}4& 0& 5\\ -1& 3& 2\end{array}\right]$
$B=\left[\begin{array}{ccc}1& 1& 1\\ 3& 5& 7\end{array}\right]$
$C=\left[\begin{array}{ccc}2& & -3\\ 0& & 1\end{array}\right]$
1) $\left(3A–B\right)=3×\left[\begin{array}{ccc}4& 0& 5\\ -1& 3& 2\end{array}\right]-\left[\begin{array}{ccc}1& 1& 1\\ 3& 5& 7\end{array}\right]=$
$=\left[\begin{array}{ccc}12& 0& 15\\ -3& 9& 6\end{array}\right]-\left[\begin{array}{ccc}1& 1& 1\\ 3& 5& 7\end{array}\right]=$
$=\left[\begin{array}{ccc}11& -1& 14\\ -6& 4& -1\end{array}\right]$
2) $\left(C\cdot \right)=\left[\begin{array}{ccc}2& & -3\\ 0& & 1\end{array}\right]\cdot =\left[\begin{array}{ccc}2& & 0\\ -3& & 1\end{array}\right]$
$\left(C\cdot B\right)=\left[\begin{array}{ccc}2& & 0\\ -3& & 1\end{array}\right]×\left[\begin{array}{ccc}1& 1& 1\\ 3& 5& 7\end{array}\right]=$
$=\left[\begin{array}{ccc}2& 2& 2\\ 0& 2& 4\end{array}\right]$
$\left(C\cdot B+A\right)=\left[\begin{array}{ccc}2& 2& 2\\ 0& 2& 4\end{array}\right]+\left[\begin{array}{ccc}4& 0& 5\\ -1& 3& 2\end{array}\right]=$
$=\left[\begin{array}{ccc}6& 2& 7\\ -1& 3& 6\end{array}\right]$

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get an expert answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?